Technetium: the unknown center of the periodic table - Strub, Erik; Badea, Désirée; Bruns, Jörn; Frontera, Antonio; Mayordomo, Natalia; Sakhonenkova, Anna; Roca Jungfer, Maximilian; Wickleder, Mathias S.; Yong, Clarence; Zegke, Markus (European journal of inorganic chemistry, 2025)
It took 78 years from Mendeleev's proposal of an existence of “eka-manganese” (1869) until it was finally named as technetium (Tc) in 1947. Another 78 years have passed since then. This provides a good occasion to pinpoint what we know and what we still do not know of this radioelement. Technetium is placed near the center of the Periodic Table, in the center of the groups 6, 7, and 8. Some chemical properties of the elements surrounding technetium show trends within the columns or along the rows of the Periodic Table, but a consistent interpretation of these trends is lacking as long as the knowledge on technetium remains incomplete. This is especially remarkable as, on the other hand, the isotope 99mTc is applied on a daily basis in nuclear medicine. The aim of this paper is to review the fundamental understanding of technetium chemistry, mostly focusing on the research of the last decade, its implications, and its future perspectives. These developments show a picture of growing connections between physicochemical data, fundamental inorganic chemistry, organometallic and coordination chemistry, computational chemistry, and geochemistry.